Knowledge and Skills in Processing of Food Materials Preventing Stunting in Early Childhood - Ismaniar, Ismaniar (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2019)
A healthy, intelligent and noble child is the dream of all parents. But to create a healthy generation, there are various problems, including many cases of stunting that occur in children, especially early childhood. Stunting is a problem of chronic malnutrition which results in growth disorders in children. Stunting factors include food patterns, parenting, and sanitation patterns. One solution to overcome the problem of stunting in children is the need for knowledge and skills in processing food ingredients and food displays. Armed with the knowledge and skills of processing and displaying food, housewives can serve nutritious and attractive food for children's consumption.